Highly selective detection of TNP over other nitro compounds in water: the role of selective host–guest interactions in Zr-NDI MOF. (5th July 2021) - Radha, Govu; Leelasree, T.; Muthukumar, D.; Pillai, Renjith S.; Aggarwal, Himanshu
Abstract : A fluorescent Zr-NDI based MOF shows the selective sensing of TNP in water, over other classes of nitro compounds. DFT studies reveal favourable host–guest interactions behind this phenomenon. Abstract : Nitroaromatics are some of the most hazardous compounds that contaminate water and are also used in explosives. The selective detection of nitroaromatics is highly warranted but at the same time very challenging. This is due to the similarities in their size, shape and functionality. However, if a system is cleverly designed to enforce selective host–guest interactions, the detection of one particular class of nitro compounds can be successfully achieved. Metal–organic frameworks (MOFs) have emerged as promising porous materials for these applications. Herein, a fluorescent Zr-NDI based MOF has been reported for the selective detection of trinitrophenol (TNP) in water. Interestingly, the high fluorescence behaviour of the MOF can be quenched only by nitrophenol derivatives, particularly TNP, whereas the other classes of nitroaromatic and nitroaliphatic compounds have no impact on the fluorescence properties of the MOF. The limit of detection of TNP is as low as 8.1 ppm and the quenching efficiency is 95%. DFT studies have been carried out in conjunction with experiments that reveal favourable host–guest interactions for the selective binding of the hydroxyl group present in TNP.